Approaches to selective fibroblast growth factor receptor 4 inhibition through targeting the ATP-pocket middle-hinge region12. Issue 8 (8th June 2017) - Fairhurst, Robin A.; Knoepfel, Thomas; Leblanc, Catherine; Buschmann, Nicole; Gaul, Christoph; Blank, Jutta; Galuba, Inga; Trappe, Jörg; Zou, Chao; Voshol, Johannes; Genick, Christine; Brunet-Lefeuvre, Peggy; et al.
Abstract : Structurally diverse covalent and non-covalent series of selective FGFR4 inhibitors have been identified. Abstract : A diverse range of selective FGFR4 inhibitor hit series were identified using unbiased screening approaches and by the modification of known kinase inhibitor scaffolds. In each case the origin of the selectivity was consistent with an interaction with a poorly conserved cysteine residue within the middle-hinge region of the kinase domain of FGFR4, at position 552. Targeting this region identified a non-covalent diaminopyrimidine series differentiating by size, an irreversible-covalent inhibitor in which Cys552 undergoes an SNAr reaction with a 2-chloropyridine, and a reversible-covalent inhibitor series in which Cys552 forms a hemithioacetal adduct with a 2-formyl naphthalene. In addition, the introduction of an acrylamide into a known FGFR scaffold identified a pan-FGFR inhibitor which reacted with both Cys552 and a second poorly conserved cysteine on the P-loop of FGFR4 at position 477 which is present in all four FGFR family members.